ANALYSIS OF THE TURBULENCE-RADIATION INTERACTION IN A METHANE-AIR DIFFUSION FLAME - Fraga, G. C.; Petry, A. P.; França, F. H. R. (Revista de Engenharia Térmica, 2018)
The phenomenon of turbulence-radiation interaction (TRI) has been demonstrated experimentally, theoretically and numerically to be important in a great number of engineering applications. This paper presents a numerical study on the subject, focusing on a methane-air diffusion flame confined in a rectangular enclosure. An open source, Fortran-based code, Fire Dynamics Simulator, is used for the analysis. Large Eddy Simulation (LES) is adopted to model the turbulence, and to resolve the sub-grid scale terms the dynamic Smagorinsky model is employed. To solve the radiative heat transfer, the finite volume method is used alongside the Weighted-Sum-of-Gray-Gases model. The main objective of the present work is to assess the magnitude of TRI effects for the configuration proposed. For this purpose, the time-averaged wall heat fluxes and volumetric radiative heat source, calculated from the LES results, are compared with those same quantities obtained by independent simulations initialized using mean temperature and species concentration fields. TRI effects are found to be responsible for differences up to 30% between results considering and neglecting turbulent fluctuations. These differences are larger for the radiative heat source and for the radiative heat flux to the walls, smaller for the total heat flux, and almost negligible for the convective heat flux. The influence of the fuel stream Reynolds number on the TRI effects is also evaluated, and a slight decrease on the magnitude of TRI is observed with the increase of that parameter.